Single-industry towns of the Russian Arctic: development strategy on the case study of the cities/towns in the Murmansk Oblast - Vladimir Vsevolodovich Didyk; Larisa Aleksandrovna Ryabova (Economic and social changes: facts, trends, forecast / Экономические и социальные перемены: факты, тенденции, прогноз, 2014)
The article is devoted to the problems of strategic management of single-industry towns’ development in the Russian Arctic. It presents brief characteristics of the government policies in relation to single-industry towns of the Russian Federation as a whole, and, particularly, of its Arctic zone. On the example of single-industry towns of the Murmansk Oblast it studies strategies of their development, typical problems to shape and implement strategic development plans